Lack of Association of rs1192415 in TGFBR3-CDC7 With Visual Field Progression: A Cohort Study in Chinese Open Angle Glaucoma Patients - Chen, Yuhong; Qiu, Chen; Qian, Shaohong; Chen, Junyi; Chen, Xueli; Wang, Li; Sun, Xinghuai (Frontiers in Genetics, 2018)
To investigate the association of known candidate genes with the visual field (VF) progression of primary open angle glaucoma (POAG) in a Han Chinese population. We included 440 POAG patients in this study. Fourteen previously reported single nucleotide polymorphisms (SNPs) at five different gene regions (TGFBR3-CDC7, TMCO1, CDKN2B-AS1, ATOH7 and SIX1/SIX6) were genotyped. Age at diagnosis, gender, intraocular pressure (IOP), mean defect (MD) of VF, vertical cup disc ratio (VCDR), best corrected visual acuity (BCVA), central corneal thickness (CCT), and axial length (AL) were recorded at baseline. Patients were followed up for five years to evaluate VF progression over time. Clinical information and allele frequencies of 14 SNPs were compared between patients who progressed and who did not within five years by multivariate logistic regression. Survival analysis was performed to evaluate the contribution of the associated SNP by cox regression. Greater MD (P < 0.0001), increased VCDR (P = 0.0001), higher IOP (P = 0.0003), worse BCVA (P = 0.002) and older age (P = 0.030) at the baseline were associated with VF progression. Both multivariate logistic regression and cox regression survival analysis showed none of the 14 SNPs statistically associated with VF progression adjusted with age at diagnosis, gender, baseline MD, follow-up IOP, CCT and AL. There were lack of association of SNPs at TGFBR3-CDC7, TMCO1, ATOH7, CDKN2B-AS1, SIX1/SIX6 loci with VF progression in POAG patients in Han Chinese. Further studies are needed to evaluate the association of genetic variants with VF progression.